The Effect of COVID-19 Pandemic on Service Sector Sustainability and Growth - Xiang, Shihui; Rasool, Saad; Hang, Yong; Javid, Kamran; Javed, Tasawar; Artene, Alin Emanuel (Frontiers in Psychology, 2021)
Coronavirus disease (COVID-19) has an unprecedented and unpredictable impact on the world's economy. The recent pandemic derives the world towards adaptively regardless of businesses, sectors, and industries. The coronavirus epidemic (COVID19) has affected the global economy and service sector. The purpose of the current study is to assess the effect of COVID-19 on service sector growth and sustainability. All the sectors and industries in the world are trying to anchor themselves amidst the COVID-19. The study focuses on the sectors that are badly hit by the outbreak and discussed the strategies and responses of different countries to sustain their economies. This study concludes that the vital role of Information Technology and digitization supports the economies to fight against the pandemic while sustaining themselves amid crises. This study also contributes to the body of knowledge by suggesting IT-based solutions for various industries to elevate effective responsiveness and avoid significant losses.